2003
DOI: 10.1530/eje.0.1490485
|View full text |Cite
|
Sign up to set email alerts
|

Resumption of methimazole after 131I therapy of hyperthyroid diseases: effect on thyroid function and volume evaluated by a randomized clinical trial

Abstract: Objective: Retrospective studies have indicated that anti-thyroid drugs (ATD) might possess a radioprotective effect, leading to a higher rate of recurrence of hyperthyroidism after iodine-131 ( 131 I) therapy. Design: A randomized clinical trial was performed to clarify whether resumption of methimazole after 131 I influences the final outcome of this treatment. Methods: We assigned 149 patients with Graves' disease or a toxic nodular goitre to groups either to resume (þATD) or not to resume (2ATD) methimazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 38 publications
1
15
0
1
Order By: Relevance
“…We did not find an adverse influence of either PTU or methimazole use. Although some retrospective studies (19 -21) have indicated that ATDs reduce the cure rate following 131 I therapy, our present results are in line with the findings in randomized studies by us and others on the use of methimazole (22)(23)(24). The fact that we were unable to demonstrate any radioprotective property of PTU is in contrast to that which has been shown by two recent prospective trials (25,26), and may be due to the relatively few patients receiving this drug.…”
Section: Outcome: Eye Symptomssupporting
confidence: 89%
“…We did not find an adverse influence of either PTU or methimazole use. Although some retrospective studies (19 -21) have indicated that ATDs reduce the cure rate following 131 I therapy, our present results are in line with the findings in randomized studies by us and others on the use of methimazole (22)(23)(24). The fact that we were unable to demonstrate any radioprotective property of PTU is in contrast to that which has been shown by two recent prospective trials (25,26), and may be due to the relatively few patients receiving this drug.…”
Section: Outcome: Eye Symptomssupporting
confidence: 89%
“…If a patient requires antithyroid drug treatment with propylthiouracil prior to radioiodine treatment, this protective effect can be overcome by stopping drug treatment 2 months beforehand or by giving a higher dose of radioiodine. Patients should avoid antithyroid drug treatment for at least 7 days after radioiodine treatment, as this is known to be without detriment to outcome, but it is not yet known if a shorter period before starting treatment is also without effect on outcome 30 . Whether propylthiouracil has any greater potential to have an adverse effect on outcome compared to carbimazole or methimazole when given after radioiodine administration is also not clear.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence to support restarting ATDs 7 days after radioiodine administration in patients considered to be at risk for cardiovascular complications, owing to the fact that thyroid hormone levels may be more stable with ATD treatment both before and after radioiodine administration [ 64 ]. Since ATDs interfere with iodine utilization by the thyroid gland, the drug must be stopped for about 3 days prior to radioiodine administration; stopping it for longer than 3 days is not necessary [ 65 ].…”
Section: Antithyroid Drug Therapy Prior To Radioiodine Treatmentmentioning
confidence: 99%